2009
DOI: 10.1001/archpediatrics.2009.167
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Women and Increases in the Risk of Diarrheal Disease and Respiratory Tract Infections in Infancy

Abstract: Objective:To explore whether different forms of violence against women were associated with increased incidence rates of diarrhea and respiratory tract infections among infants.Design: A 12-month follow-up study embedded in a food and micronutrient supplementation trial.Setting: Rural Bangladesh.Participants: Pregnant women and their 3132 liveborn children.Main Exposure: Maternal exposure to physical, sexual, and emotional violence and level of controlling behavior in the family. Main Outcome Measures:Infants'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
(47 reference statements)
6
14
0
Order By: Relevance
“…In addition, controlling behavior might impair child linear growth by increasing the risk of lower respiratory tract infections and diarrheal diseases during the first year of life [4], which is in line with previous studies reporting that increased infectious illness frequency and severity are associated with poor growth [30,31]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, controlling behavior might impair child linear growth by increasing the risk of lower respiratory tract infections and diarrheal diseases during the first year of life [4], which is in line with previous studies reporting that increased infectious illness frequency and severity are associated with poor growth [30,31]. …”
Section: Discussionsupporting
confidence: 82%
“…Intimate Partner Violence (IPV) is a widespread public health problem that affects millions of women worldwide [1] and has severe physical and mental health consequences for mothers [2] and their children [3,4]. Women who experience physical or sexual IPV are often also exposed to a high level of controlling behavior by their partners [1].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Bangladesh convincingly showed that children of women exposed to IPV have greater exposure to potentially dangerous conditions like diarrhea and Acute Respiratory Infection (ARI) [ 4 , 36 ]. Impact of IPV on child nutrition has also been demonstrated by a few studies [ 3 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…2003). Higher odds of diarrhoea, respiratory tract infection and acute infant illnesses have been observed among the children of mothers who were exposed to IPV in Bangladesh (Asling‐Monemi et al . 2009a; Silverman et al .…”
Section: Introductionmentioning
confidence: 99%